Respostas

A melhor resposta!
2014-07-30T10:39:03-03:00
Olá, Rodriwam!

6.
a) x² - 6x - 16 = 0
a = 1
b = -6
c = -16

Δ = b² - 4.a.c
Δ = (-6)² - 4.1.(-16)
Δ = 36 + 64
Δ = 100

-b +- √Δ / 2.a
-(-6) +- √100 / 2.1
6 +- 10 / 2

x' = 6+10/2 = 16/2 = 8
x'' = 6-10/2 = -4/2 = -2

S = {8, -2}

b) 6x² - x - 5 = 0
a = 6
b = -1
c = -5

Δ = b² - 4.a.c
Δ = (-1)² - 4.6.(-5)
Δ = 1 + 120
Δ = 121

-b +- √Δ / 2.a
-(-1) +- √121 / 2.6
1 +- 11 / 12

x' = 1+11/12 = 12/12 = 1
x'' = 1-11/12 = -10:2/12:2 = -5/6

S = {1, -5/6}



1 5 1
valeu pela ajuda , mas teria como resolver a questao 7 tambem ? =D